The practical and theoretical implications of pretreatment and posttreatment anxiety levels in alcoholic in-patients - Thomson, Peter R S (Rhodes University, Faculty of Humanities, Department of Psychology, 1984)
Pretreatment and posttreatment anxiety scores on the IPAT Anxiety Inventory and the Taylor Manifest Anxiety Scale were obtained from 27 alcoholic in-patients who participated in an alcoholic treatment programme. The treatment programme focused on abstinence and not on anxiety reduction. The results showed that there was a significant decrease between the pre- and the posttreatment anxiety scores on both measures . The duration of hospitalization or the attendance of group psychotherapy did not affect the decrease in anxiety scores. The implications of these results for Pattison's (1979) Multivariate Multimodal model of alcoholism are discussed.
Keywords: Uncatalogued